Premarital Check Up dalam Perspektif Maqashid al-Syari’ah - Khusni Tamrin (Al-Manhaj, 2021)
Premarital health check-up is a preventive measure to avoid unwanted things, in order to form a family and produce perfect offspring. In this paper aims to discuss premarital health tests (premarital check up) perspective maqâshid al-syarî'ah. In this research the method used is a qualitative research method, the type of research research, with a philosophical approach and medical approach, the theory of al-shari'ah maqasid. Based on the results of the study it was found that, conducting pre-marital health tests it can be known earlier various possible illnesses suffered so that action can be taken earlier to prevent various difficulties that will come, this is in accordance with the theory of Saad ad-dzarî'ah or taking steps preventive from anything that can threaten. In the analysis of sharia maqasid, namely guarding religion (hifzh dîn), guarding the soul (hifzh nafs), guarding offspring (hifzh nasl), guarding reason (hizfh 'aql) and protecting wealth (hizfh mâl), pre-marital health tests in this case are more emphasized by guarding the soul (hifzh nafs) and guarding offspring (hifzh nasl). Pre-marital medical tests in the view of Maqâshid Al-Syarî'ah are recommended because they see the many benefits in the examination.